Assessing the Status and Challenges of Sole Proprietor Garment Businesses: Insights for Operational Enhancement - Ma. Elena C. Estebal; Merlina B. Natividad (Logistic and Operation Management Research (LOMR), 2024)
A sole proprietorship is without a doubt, the simplest form of business organization. Garment business on the other hand is considered as one of the most popular ventures among women entrepreneurs in the Philippines. This study aimed to determine the status, issues and concerns of sole garment business in Taguig City to serve as basis for a proposal towards enhanced operations. It also attempted to determine the issues and concerns encountered in women entrepreneurs and their employees in the course of running the business. The descriptive method of research was used and it involved twelve (12) proprietors and fifty (50) employees as respondents. The data were analyzed and interpreted using the frequency, percentage, weighted mean and t-test. Results revealed that the respondents strongly agree on objective of the sole garment business, personnel, capital investments, operations requirements, wages and benefits, and supply of raw materials as vital factors for enhanced operations of sole garment business. The null hypothesis that there is no significant difference between the perceptions of the proprietors and employees on the status of sole garment business was accepted when it came to personnel, capital investments, operations requirements and wages and benefits. However, such null hypothesis was rejected when it came to objectives, raw materials supply, and equipment. As to issues and concerns encountered in sole garment business, the need for technologically advanced equipment came first, management style was ranked second, keeping up with fast fashion trend came in third while supply of raw materials was ranked fourth and inadequacy of business capitals came in the fifth rank.